Effect of mechanical and physical properties on dust-producing characteristics of rocks from Zonguldak coal basin, Turkey - T. Guyaguler (The Institute of Materials, Minerals and Mining, 1905)
An analytical technique using computer-based multiple-regression methods was employed to determine the relation between the dust-producing index and inherent rock properties of typical samples from a coal-producing area, one of the aims being to provide a preliminary predictive tool for practical use. The investigation demonstrated that factors varied in their influence under different conditions, the brittleness:toughness ratio and the hardness being the most significant inherent properties with hardness showing the highest positive correlation coefficient